2006
DOI: 10.1038/modpathol.3800609
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear BCL-10 expression is common in lymphoplasmacytic lymphoma/Waldenström macroglobulinemia and does not correlate with p65 NF-κB activation

Abstract: B-cell lymphoma 10 (BCL-10) is expressed in the cytoplasm of normal germinal center and marginal zone Bcells and is involved in lymphocyte development and activation. Aberrant nuclear expression of BCL-10 occurs in a subset of extranodal marginal zone B-cell lymphomas (MALT lymphomas), primarily those with the t(1;14)(p22;q32) or t(11;18)(q21;q21). Little is known about BCL-10 expression in lymphoplasmacytic lymphoma/ Waldenströ m macroglobulinemia (LPL/WM). We assessed for BCL-10 in 51 bone marrow (BM) specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
(50 reference statements)
3
12
0
Order By: Relevance
“…BCL-10 immunostaining in breast MALT lymphomas is discordant with these results, but nuclear BCL-10 staining has been reported in extra-mammary MALT lymphomas without the t(11;18) in other studies. 14,[17][18][19] Thus, our results support those of others and suggest that moderate nuclear BCL-10 immunostaining overestimates the percentage of neoplasms that carry MALT1 gene rearrangements. The BCL-10 and NF-kB data in primary breast diffuse large B-cell lymphomas shows that this group is heterogeneous, with most cases showing weak cytoplasmic BCL-10 staining and a subset of cases showing evidence of NF-kB activation, unlike breast MALT lymphomas.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…BCL-10 immunostaining in breast MALT lymphomas is discordant with these results, but nuclear BCL-10 staining has been reported in extra-mammary MALT lymphomas without the t(11;18) in other studies. 14,[17][18][19] Thus, our results support those of others and suggest that moderate nuclear BCL-10 immunostaining overestimates the percentage of neoplasms that carry MALT1 gene rearrangements. The BCL-10 and NF-kB data in primary breast diffuse large B-cell lymphomas shows that this group is heterogeneous, with most cases showing weak cytoplasmic BCL-10 staining and a subset of cases showing evidence of NF-kB activation, unlike breast MALT lymphomas.…”
Section: Discussionsupporting
confidence: 81%
“…The explanation for this apparent discordance is uncertain, but others have reported moderate nuclear BCL-10 immunoreactivity in MALT lymphomas without the t (11;18). 14,[16][17][18][19] More specifically, although moderate nuclear staining for BCL-10 is usually observed in MALT lymphomas with the t(11;18), up to 20-50% of MALT lymphomas without the t(11;18) also show moderate nuclear BCL-10 positivity. Thus, although BCL-10 immunostaining can be used as an initial screen for the t(11;18) in MALT lymphomas, the presence of BCL-10 nuclear expression should not be used as a surrogate for the presence of the t (11;18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ours and other previous findings have shown that different domains at HBx-COOH may represent various mechanisms, and the mutations may directly affect the proliferation and invasion by regulating the cell cycle and inducing the expression of p21 WAF1 , p14 ARF and MDM2 (13). This supports the hypothesis that deleted forms of HBx may contribute to liver carcinogenesis (13,(30)(31)(32). Our previous findings also demonstrated that CENP-A overexpression was correlated with serum HBsAg states in HCC patients (16).…”
Section: Discussionsupporting
confidence: 73%
“…9,10 Data for its role in WM are limited, but there is some evidence to suggest that NF-B is activated in WM cells. 11,12 The PI3K/Akt pathway acts as a critical regulator of cell survival by stimulating cell proliferation and inhibiting apoptosis, [13][14][15] and has been implicated in the pathogenesis of various cancers, including lymphoproliferative disorders. [16][17][18] Akt indirectly activates NF-B through direct phosphorylation and activation of IB kinase alpha (IKK␣), thereby inducing degradation of NF-B inhibitor alpha (IB␣) by the ubiquitineproteasome pathway.…”
Section: Introductionmentioning
confidence: 99%